PENGARUH OPERATING CAPACITY, SALES GROWTH DAN ARUS KAS OPERASI TERHADAP FINANCIAL DISTRESS - Annisa Livia Ramadhani; Khairun nisa (Program Studi Akuntansi, Universitas Kuningan, 2019)
This study aims to determine how the influence of operating capacity, sales growth and operating cash flows on financial distress. The population in this study israll agricultural sector companies listed on the Indonesia Stock Exchange (IDX) in 2013-2017. The sampling technique in this study used purposive sampling which produced 8 samples in a period of 5 years, namely as many as 40 units of data samples. The analytical method used is logistic regression analysis which is processed. using SPSS Version 25. Based on the results of this study, it was found that simultaneous operating capacity, sales growth and operating cash flows influence the occurrence of financial distress. Then partially, operating capacity and sales growth have no effect on the occurrence of financial distress, while operating cash flows have a positive and significant effect on the occurrence of financial distress. Keyword : Financial Distress, Operating capacity, Sales growth, Operation cash flow.